65 YEARS OF THE DOUBLE HELIX: Genetics informs precision practice in the diagnosis and management of pheochromocytoma. Issue 8 (August 2018) - Neumann, Hartmut P; Young, William F; Krauss, Tobias; Bayley, Jean-Pierre; Schiavi, Francesca; Opocher, Giuseppe; Boedeker, Carsten C; Tirosh, Amit; Castinetti, Frederic; Ruf, Juri; Beltsevich, Dmitry; Walz, Martin; et al.
Abstract : Although the authors of the present review have contributed to genetic discoveries in the field of pheochromocytoma research, we can legitimately ask whether these advances have led to improvements in the diagnosis and management of patients with pheochromocytoma. The answer to this question is an emphatic Yes ! In the field of molecular genetics, the well-established axiom that familial (genetic) pheochromocytoma represents 10% of all cases has been overturned, with >35% of cases now attributable to germline disease-causing mutations. Furthermore, genetic pheochromocytoma can now be grouped into five different clinical presentation types in the context of the ten known susceptibility genes for pheochromocytoma-associated syndromes. We now have the tools to diagnose patients with genetic pheochromocytoma, identify germline mutation carriers and to offer gene-informed medical management including enhanced surveillance and prevention. Clinically, we now treat an entire family of tumors of the paraganglia, with the exact phenotype varying by specific gene. In terms of detection and classification, simultaneous advances in biochemical detection and imaging localization have taken place, and the histopathology of the paraganglioma tumor family has been revised by immunohistochemical-genetic classification by gene-specific antibody immunohistochemistry. Treatment options have also been substantially enriched by the application of minimally invasive and adrenal-sparing surgery. Finally and most importantly, it is now widely recognized that patients with genetic pheochromocytoma/paraganglioma syndromes should be treated in specialized centers dedicated to the diagnosis, treatment and surveillance of this rare neoplasm.